2017
DOI: 10.1007/s12602-017-9273-y
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Probiotic Lactobacilli Inclusion in Helping Piglets Establish Healthy Intestinal Inter-environment for Pathogen Defense

Abstract: The gastrointestinal tract of pigs is densely populated with microorganisms that closely interact with the host and with ingested feed. Gut microbiota benefits the host by providing nutrients from dietary substrates and modulating the development and function of the digestive and immune systems. An optimized gastrointestinal microbiome is crucial for pigs' health, and establishment of the microbiome in piglets is especially important for growth and disease resistance. However, the microbiome in the gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 103 publications
0
44
0
3
Order By: Relevance
“…and growth performance has been confirmed (Hou et al, 2016). Moreover, Lactobacillus species are common probiotics, and they play important roles in pathogen defense, and improve intestinal barrier function and immunity in piglets (Yang et al, 2017). Faecalibacterium prausnitzii is one of the most abundant butyrate-producing bacterium in the intestinal tract and has been demonstrated as a microbial biomarker of intestinal homeostasis (Miquel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and growth performance has been confirmed (Hou et al, 2016). Moreover, Lactobacillus species are common probiotics, and they play important roles in pathogen defense, and improve intestinal barrier function and immunity in piglets (Yang et al, 2017). Faecalibacterium prausnitzii is one of the most abundant butyrate-producing bacterium in the intestinal tract and has been demonstrated as a microbial biomarker of intestinal homeostasis (Miquel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus was one of the most dominant genera, accounting for approximately 15% of the 16S rRNA gene sequences from porcine intestinal samples, regardless of age (36). Moreover, Lactobacillus species are common probiotics, and they play important roles in pathogen defense and improve intestinal barrier function and immunity in piglets (37). Importantly, our results revealed that the growth rate and plasma concentrations of GH and IGF-1 were increased, but diarrhea rates were decreased, in piglets from SF-fed sows.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to look for alternative ways to combat infections with this foodborne pathogen [36,37]. One possibility is the modulation of the GIT microbiota by commensal and probiotic bacteria [38].…”
Section: Introductionmentioning
confidence: 99%